The Gig Economy and its Implications to Corporate Social Responsibility: Evidence from the UK. - Pasanting, Arvy (2019)
Organisations face one of the most critical challenges of the 21st century. These challenges focus on the moral dilemma typified by digital platforms, and their lack of regard for the ethical and moral considerations by obfuscating national regulatory frameworks guiding labour rights and protection. As technological advances create a renewed conundrum on how businesses should be regulated, a renewed principles-based approach must be set to enhance responsible corporate action. It also raises further arguments of the need for more regulations to address regulatory gaps guiding employment rights in the UK.